Research Progress in Natural Products against Liver Fibrosis - Zhao, Siyu; Chen, Xin; Tan, Rui; Wu, Xiaoqing; Jiang, Hezhong (Natural Products Journal, The, 2025)
Fibrosis of the liver is the most common pathological feature of many chronic liver diseases, progressing to cirrhosis and eventually liver cancer. Currently, only individual genes or proteins are targeted by synthetic drugs used to treat liver fibrosis, they have limited therapeutic effect, and are associated with many side effects. In contrast, natural products have shown great advantages and potential in the treatment of liver fibrosis due to their structural diversity, high multi-target activity and low toxicity and side effects. Therefore, this review concludes the pathological mechanism of liver fibrosis and the cellular and signaling pathways involved, provides new ideas for anti-liver fibrosis research and introduces common natural products and their anti-hepatic fibrosis mechanisms.
Keywords: natural products